Integration Questions

Question Number 6107 by gourav~ last updated on 14/Jun/16

$$\int\frac{{x}}{{x}^{\mathrm{3}} +{x}+\mathrm{2}}{dx}\:=? \\$$

Commented by Yozzii last updated on 14/Jun/16

$${x}^{\mathrm{3}} +{x}+\mathrm{2}={x}^{\mathrm{3}} +\mathrm{1}+{x}+\mathrm{1} \\$$$$=\left({x}+\mathrm{1}\right)\left({x}^{\mathrm{2}} −{x}+\mathrm{1}\right)+{x}+\mathrm{1} \\$$$$=\left({x}+\mathrm{1}\right)\left({x}^{\mathrm{2}} −{x}+\mathrm{1}+\mathrm{1}\right) \\$$$${x}^{\mathrm{3}} +{x}+\mathrm{2}=\left({x}+\mathrm{1}\right)\left({x}^{\mathrm{2}} −{x}+\mathrm{2}\right) \\$$$$\frac{{x}}{\left({x}+\mathrm{1}\right)\left({x}^{\mathrm{2}} −{x}+\mathrm{2}\right)}\equiv\frac{{a}}{{x}+\mathrm{1}}+\frac{{bx}+{c}}{{x}^{\mathrm{2}} −{x}+\mathrm{2}} \\$$$${x}\equiv{a}\left({x}^{\mathrm{2}} −{x}+\mathrm{2}\right)+\left({x}+\mathrm{1}\right)\left({bx}+{c}\right) \\$$$${x}\equiv{ax}^{\mathrm{2}} −{ax}+\mathrm{2}{a}+{bx}^{\mathrm{2}} +{cx}+{bx}+{c} \\$$$$\mathrm{0}{x}^{\mathrm{2}} +{x}+\mathrm{0}\equiv\left({a}+{b}\right){x}^{\mathrm{2}} +\left({b}+{c}−{a}\right){x}+\mathrm{2}{a}+{c} \\$$$$\Rightarrow{a}=−{b} \\$$$$\Rightarrow{b}+{c}−{a}=\mathrm{1} \\$$$$\Rightarrow{c}=−\mathrm{2}{a} \\$$$$\therefore{c}=\mathrm{2}{b} \\$$$$\therefore{b}+\mathrm{2}{b}+{b}=\mathrm{1}\Rightarrow{b}=\mathrm{1}/\mathrm{4} \\$$$$\therefore{a}=−\mathrm{1}/\mathrm{4} \\$$$$\therefore{c}=\mathrm{1}/\mathrm{2} \\$$$$\therefore\frac{{x}}{{x}^{\mathrm{3}} +{x}+\mathrm{2}}=\frac{−\mathrm{1}}{\mathrm{4}\left({x}+\mathrm{1}\right)}+\frac{{x}+\mathrm{2}}{\mathrm{4}\left({x}^{\mathrm{2}} −{x}+\mathrm{2}\right)} \\$$$$\\$$$$\\$$

Answered by Yozzii last updated on 14/Jun/16

$${Let}\:{I}=\int\frac{{x}}{{x}^{\mathrm{3}} +{x}+\mathrm{2}}{dx}=\frac{\mathrm{1}}{\mathrm{4}}\int\left(\frac{−\mathrm{1}}{{x}+\mathrm{1}}+\frac{{x}+\mathrm{2}}{{x}^{\mathrm{2}} −{x}+\mathrm{2}}\right){dx} \\$$$${I}=\frac{\mathrm{1}}{\mathrm{4}}\int\left(\frac{−\mathrm{1}}{{x}+\mathrm{1}}+\frac{\mathrm{2}{x}−\mathrm{1}}{\mathrm{2}\left({x}^{\mathrm{2}} −{x}+\mathrm{2}\right)}+\frac{\mathrm{5}}{\mathrm{2}\left({x}^{\mathrm{2}} −{x}+\mathrm{2}\right)}\right){dx} \\$$$${x}^{\mathrm{2}} −{x}+\mathrm{2}={x}^{\mathrm{2}} −\mathrm{2}×\mathrm{0}.\mathrm{5}{x}+\mathrm{0}.\mathrm{5}^{\mathrm{2}} −\mathrm{0}.\mathrm{5}^{\mathrm{2}} +\mathrm{2}=\left({x}−\frac{\mathrm{1}}{\mathrm{2}}\right)^{\mathrm{2}} +\frac{\mathrm{7}}{\mathrm{4}} \\$$$${I}=\frac{\mathrm{1}}{\mathrm{4}}\int\left(\frac{−\mathrm{1}}{{x}+\mathrm{1}}+\frac{\mathrm{1}}{\mathrm{2}}\left(\frac{\frac{{d}}{{dx}}\left({x}^{\mathrm{2}} −{x}+\mathrm{2}\right)}{{x}^{\mathrm{2}} −{x}+\mathrm{2}}\right)+\frac{\mathrm{5}}{\mathrm{2}}×\frac{\mathrm{1}}{\frac{\mathrm{7}}{\mathrm{4}}+\left({x}−\frac{\mathrm{1}}{\mathrm{2}}\right)^{\mathrm{2}} }\right){dx} \\$$$${I}=\frac{\mathrm{1}}{\mathrm{4}}\left(−{ln}\mid{x}+\mathrm{1}\mid+\frac{\mathrm{1}}{\mathrm{2}}{ln}\mid{x}^{\mathrm{2}} −{x}+\mathrm{2}\mid+\frac{\mathrm{5}}{\mathrm{2}}×\frac{\mathrm{1}}{\frac{\sqrt{\mathrm{7}}}{\mathrm{2}}}{tan}^{−\mathrm{1}} \left(\frac{{x}−\frac{\mathrm{1}}{\mathrm{2}}}{\frac{\sqrt{\mathrm{7}}}{\mathrm{2}}}\right)\right)+{C} \\$$$${I}=\frac{\mathrm{1}}{\mathrm{4}}{ln}\mid\frac{\sqrt{{x}^{\mathrm{2}} −{x}+\mathrm{2}}}{{x}+\mathrm{1}}\mid+\frac{\mathrm{5}}{\mathrm{4}\sqrt{\mathrm{7}}}{tan}^{−\mathrm{1}} \left(\frac{\mathrm{2}{x}−\mathrm{1}}{\sqrt{\mathrm{7}}}\right)+{C} \\$$